2018
DOI: 10.1371/journal.pone.0195229
|View full text |Cite
|
Sign up to set email alerts
|

The performance of the IES-R for Latinos and non-Latinos: Assessing measurement invariance

Abstract: Violent acts on university campuses are becoming more frequent. Enrollment rates of Latinos at universities is increasing. Research has indicated that youths are more susceptible to trauma, particularly Latinos. Thus, it is imperative to evaluate the validity of commonly used posttraumatic stress measures among Latino college students. The Impact of Event Scale-Revised (IES-R) is one of the most commonly used metrics of posttraumatic stress disorder symptomatology. However, it is largely unknown if the IES-R i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 63 publications
1
45
0
Order By: Relevance
“…Items are rated on a 5-point scale ranging from 0 ("not at all") to 4 ("extremely"). The IES-R yields a total score ranging from 0 to 88, with scores of 33 or higher reflect probable PTSD [55]. Within this sample, Cronbach's α was 0.92 for the total scale, 0.85 for the intrusive thoughts, 0.80 for the hyperarousal, and 0.76 for the avoidance subscales.…”
Section: Post-traumatic Stress Disorder Symptomsmentioning
confidence: 94%
“…Items are rated on a 5-point scale ranging from 0 ("not at all") to 4 ("extremely"). The IES-R yields a total score ranging from 0 to 88, with scores of 33 or higher reflect probable PTSD [55]. Within this sample, Cronbach's α was 0.92 for the total scale, 0.85 for the intrusive thoughts, 0.80 for the hyperarousal, and 0.76 for the avoidance subscales.…”
Section: Post-traumatic Stress Disorder Symptomsmentioning
confidence: 94%
“…The total IES-R score was used to perform the inferential statistics, whereas for descriptive statistics, the total IES-R score was divided into normal (0-23), mild (24)(25)(26)(27)(28)(29)(30)(31)(32), moderate (33)(34)(35)(36), and severe psychological distress (>37). 22 The mental health status was assessed by the Depression, Anxiety, and Stress Scale (DASS-21). This scale has been used previously in research related to outbreaks as H1N1, 23 SARS, 24 and recently, in COVID-19 outbreak in china (20).…”
Section: Surveymentioning
confidence: 99%
“…Questions 1,6,8,11,12,14, and 18 formed the stress subscale. The total stress subscale score was divided into normal (0-10), mild stress (11)(12)(13)(14)(15)(16)(17)(18), moderate stress (19)(20)(21)(22)(23)(24)(25)(26), severe stress (27-34), and extremely severe stress (35)(36)(37)(38)(39)(40)(41)(42). 20…”
Section: Surveymentioning
confidence: 99%
“…We applied the Impact of Event Scale-Revised (IES-R), which evaluates the emotional distress that accompanies an inherently stressful occurrence, such as violence, abuse, or natural disasters. 9 The IES-R reports three factors to characterize the emotional distress of an event: intrusive thoughts (8 items), avoidance (8 items), and hyperarousal (6 items). Given that these factors are symptoms central to PTSD, the revised scale determined cut-off points to suggest the presence of clinically significant PTSD, which is a total score of 35 or more.…”
Section: Surveymentioning
confidence: 99%
“…Concerning sociodemographic characteristics, being female, younger, and single were significant factors. Studies in China have not found differences according to 343 (17) 188 (9) 1531 (74)…”
Section: P=0012mentioning
confidence: 99%